Securitização e política de exceção: o excepcionalismo internacionalista norte-americano na segunda Guerra do Iraque - Motta, Bárbara Vasconcellos de Carvalho [UNESP] (2014)
After the attacks of September 11, 2001, the U.S. government intensified the process of securitization in response to the fundamentalist terrorism within the framework of the war on terror, identifying it as an existential threat to the United States. Immediate initiatives were taken, after sanctioning the Patriot Act, which increased the power of repressive action and that allowed military interventions in Afghanistan, in 2001, and Iraq in 2003. Exceptionality acts enable states to provide quick responses to emergency issues on the international scene. The choice of exception, as a political choice, is marked by a series of ideational components that contributed to that decision. Therefore, in the case of the second Iraq War the understanding of the securitization process can only be complete if taken into consideration both the political process and the ideational foundations that conformed the securitizing movement. The consideration of these factors is also crucial to ascertain the antinomies and weaknesses of securitization theory when applied to this case.